Severe Vision Impairment and Its Association with COVID-19 Susceptibility, Severity, and Mortality: A Population-Based Cohort Study - Young Kook Kim; Su Hwan Kim; June Ho Lee; Chae Young Oh; Hajoung Lee; Goneui Kang; Sooyeon Choe; Jieun Cheon; Hyung-Jin Yoon; Ahnul Ha (Journal of Clinical Medicine, 2026)
Background/Objectives: We investigated the associations of severe vision impairment (SVI) with SARS-CoV-2 infection and COVID-19 outcomes using the nationwide K-COV-N database, which links Korea Disease Control and Prevention Agency SARS-CoV-2 testing records with National Health Insurance Service data. Methods: Adults aged ≥20 years with laboratory-confirmed SARS-CoV-2 infection and matched controls who either tested negative or were untested but had no documented SARS-CoV-2 infection between 8 October 2020, and 31 December 2021, were included. Pre-existing SVI was defined using an inclusive algorithm based on either a best-corrected visual acuity